Infrared Thermography and Physiological Variables as Methods for Recognizing Fear in Domestic Cats (Felis catus) Using Three Pharmacological Models: Cannabidiol, Gabapentin, and Synthetic Facial Pheromones - Fabiola Torres-Bernal; Julio Martínez-Burnes; Ismael Hernández-Avalos; Adriana Olmos-Hernández; Adriana Domínguez-OIiva; Brenda Reyes-Sotelo; Cynthia González-López; Diana Villanueva-Pereyra; Daniel Mota-Rojas (Veterinary Sciences)
This study aimed to assess changes in the surface temperature and physiological parameters of cats exposed to a fear model involving negative dog–cat interactions, receiving three pharmacological options: a single dose of cannabidiol, gabapentin, or synthetic facial pheromones. The surface temperature of the upper and lower limbs, facial, dorsal, and appendicular thermal windows was assessed through infrared thermography. Additionally, heart rate, respiratory rate, and rectal temperature were recorded. Eighty male and female domestic cats were included in the study and randomly divided into four groups: CONTROL (placebo, 2 mL/cat orally), CBD (cannabidiol, 2 mg/kg orally), GABA (gabapentin, 100 mg/cat orally), and SFP (synthetic facial pheromone, two sprays/carrier). All cats underwent six experimental phases: Tbasal−, T1stfear, T1strecovery, Tbasal+, T2ndfear, and T2ndrecovery. Drug administration was carried out at the end of T1strecovery; the time between drug administration and Tbasal+ differed according to each drug’s nature. Statistical differences were obtained between experimental groups and times in the average surface temperature of thermal windows and cardiorespiratory parameters. In particular, the CBD, GABA, and SFP groups exhibited differences during T2ndfear, in contrast to the control and T1stfear groups. In conclusion, the results suggest a pharmacological effect of CBD, GABA, and SFP on cats’ physiological alterations in response to fear.